The Impact of Virtual Try-On Tools for Beauty Products on Consumer Behavior: A Segmentation Study. - Zarkada, Anna K.; Barakat, Suzanne; Melanthiou, Yioula (My University, 2025)
We present the characteristics of Virtual try-on tools (VTOs) with an emphasis on digital mirrors used by the beauty industry and review the extant knowledge on the mechanism by which they influence consumer behavior. We utilize a quasi-experimental empirical research design through which 221 self-identified as female participants tested the VTO of a luxury makeup brand and then completed a survey of their socio-demographics, attitudes, and behaviors. Two segments emerge, the hedonic enthusiasts and the utility-focused consumers. Their characteristics are analyzed, and the insights are utilized to draw recommendations for marketers in the beauty industry. This is one of the first studies of how VTOs influence consumer behavior in the beauty industry and the first attempt at segmenting their users.
Keywords: Consumer Behavior; Marketing; Fan and Audience Studies